Eosinophilia, a marker of asymptomatic Strongyloides infection, in a young patient with extrapulmonary tuberculosis. (4th January 2018) - Yamanashi, Hirotomo; Kanbara, Sinsuke; Murase, Kunihiko; Maeda, Takahiro
Abstract : Strongyloides stercoralis infection is a common and neglected public health problem in many areas of the world. Here we report the case of a 21-year-old woman who emigrated from Cambodia to Japan and presented with swelling of the right supraclavicular region of 2 months' duration. She had no other symptoms. Tuberculous lymphadenitis was diagnosed based on a fine-needle aspiration biopsy of the right supraclavicular lymph node. The laboratory examination revealed mild eosinophilia (eosinophils 1348/µL). S. stercoralis and Hymenolepis nana were detected serologically and in faeces examination. This case demonstrates that clinicians should search for S. stercoralis infection in patients with tuberculosis who have epidemiological risk factors and/or laboratory signs of eosinophilia, even if other symptoms and signs of helminths infection are less obvious.